Insidensi dan Risiko Penularan Avian Influenza pada Peternakan Ayam Petelur di Kabupaten Pinrang - Sri Wahyuni; Ardilasunu Wicaksono; Agik Suprayogi (Jurnal Ilmu Pertanian Indonesia, 2022)
Avian Influenza (AI) is an infectious disease on poultry with a high mortality rate, caused by Avian Influenza type A viruses from the family Orthomyxoviridae. For the layer chicken, the negative impacts of AI are the decrease of egg production until the death. The aims of the study were to analyze disease’s case data, measure the spread of disease, describe the distribution of disease, and mapping the risk of AI occurrence. The data were collected from the records of Dinas Peternakan dan Perkebunan by conducting interviews using the structured questionnaires. The data were analysed by calculating the incidence rate and performing a geographic information system (GIS) for mapping. The results showed that the highest incidence rate among sub-districts for 3 years was in Mattiro Sompe sub-district of 2.015 cases per 10.000 animals-year, while the lowest incidence rate among 3 sub-districts for 3 years was in Duampanua, Lanrisang, and Mattiro Bulu sub-districts of 0 case per 10.000 animals-year. The highrisk district was Mattiro Sompe Subdistrict, so that the control measures need to be emphasized in this area by increasing the biosecurity practices, depopulation and stamping out in new infected area, vaccination, surveillance, routine socialization, monitoring, and provide additional animal health facilities and human resources, especially the veterinarians, to optimize the disease control measures. Keywords: Avian Influenza (AI), incidence rate, layer chicken, Pinrang district